The Motif of Education in Sentimental Narrative. - Barreiro García, Fernando (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2013)
The motif of education is important in sentimental literature and in eighteenth-century narrative. It is both a central issue in terms of social reform in an enlightened sense, and a focal point in the love and courtship themes which are present in such narrative, the so-called seduction plot. It appears as a frequent topic in many authors of English, French, German and Spanish literature. The connection between the issue of education and the seduction plot is observed in the protagonists of the latter, especially in the male main character, either a libertine villain or a lovable but rakish seducer, whose personality has been influenced by a deficient education. Furthermore, such literature shows a concern more specifically focused on education, also discernible in journalism and theatre. It deals with topics such as the functionality of education itself and the pedagogy used both in public schools and in education at home with a tutor, mostly presented from a progressive perspective, usually influenced by the work of Rousseau. The progressive tendency of the sentimental novel becomes a radical discourse in the feminist and Jacobin novel of the end of the eighteenth century.